Functionalization of BaTiO3 nanoparticles with electron insulating and conducting organophosphazene-based hybrid materials. Issue 32 (3rd April 2017) - Pappas, George S.; Wan, Chaoying; Bowen, Chris; Haddleton, David M.; Huang, Xiaobin
Abstract : Structuring of core–shell dielectric nanoparticles. Abstract : Novel core–shell structured organophosphazene (OPZ) coated BaTiO3 nanoparticles (OPZ@BaTiO3 ) were produced via a facile and rapid one-step nucleophilic substitution reaction in ambient conditions. The morphology, structure and textural properties of the core–shell nanoparticles were analysed via electron microscopy, spectroscopy, thermogravimetry and porosimetry, and the dielectric properties were evaluated by impedance spectroscopy. The thickness of the cross-linked OPZ shell was readily tailored by varying the weight ratio of the OPZ monomers to BaTiO3, which in turn affected the relative permittivity and the frequency dependence of the OPZ/BaTiO3 particles. A subsequent carbonisation treatment of the OPZ@BaTiO3 at 700 °C transformed the polymeric OPZ shell to a microporous carbonaceous shell, which dramatically increased the electrical conductivity of the particles. Organophosphazene chemistry offers a facile route to functionalise BaTiO3 nanoparticles without any pre-treatment, and generate a range of core–shell BaTiO3 nanoparticles with tailored dielectric and electrically conductive properties that can be used as active fillers for polymer based nanocomposites and energy storage applications. The effectiveness and advantages of OPZ chemistry over other reported methods in forming core–shell particles are demonstrated.